Temporal and Spatial Assessment of Glacier Elevation Change in the Kangri Karpo Region Using ASTER Data from 2000 to 2024 - Qihua Wang; Yuande Yang; Jiayu Hu; Jianglong Zhang; Zuqiang Li; Yuechen Wang (Atmosphere)
Temperate glaciers in the Kangri Karpo region of the southeastern Qinghai–Tibet Plateau (QTP) have experienced significant ablation in recent decades, increasing the risk of glacier-related hazards and impacting regional water resources. However, the spatial and temporal pattern of mass loss in these glaciers remains inadequately quantified. In this study, we used ASTER L1A stereo images to construct a high-resolution elevation time series and provide a comprehensive spatial–temporal assessment of glacier elevation change from 2000 to 2024. The results indicate that almost all glaciers have experienced rapid ablation, with an average surface elevation decrease of −18.35 ± 5.13 m, corresponding to a rate of −0.76 ± 0.21 m yr−1. Glaciers in the region were divided into the northern and southern basins, with average rates of −0.79 ± 0.17 m yr−1 and −0.72 ± 0.13 m yr−1, respectively. A notable difference in acceleration trends between the two basins was observed, with the elevation rate increasing from −0.78 ± 0.17m yr−1 to −1.04 ± 0.17 m yr−1 and from −0.52 ± 0.13 m yr−1 to −0.92 ± 0.13 m yr−1, respectively. The seasonal cycle was identified in glacier surface elevation change, with an accumulation period from November to March followed by a prolonged ablation period. The seasonal amplitude decreased with elevation, with higher elevations exhibiting longer accumulation periods and less ablation. Correlation analysis with meteorological data indicated that higher summer temperatures and increased summer rainfall intensify elevation loss, while increased spring snowfall may reduce ablation. Our analysis highlights distinct variations in glacier elevation changes across different locations, elevations, and climatic conditions in the Kangri Karpo region, providing valuable insights into glacier responses to environmental changes on the Tibetan Plateau.